2017
DOI: 10.1111/apa.14008
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic drug monitoring was helpful in guiding the decision‐making process for children receiving infliximab for inflammatory bowel disease

Abstract: Aim This study examined the impact of therapeutic drug monitoring (TDM) on clinical decision‐making for children receiving infliximab for inflammatory bowel disease (IBD). Methods The medical records of children with IBD who had infliximab trough levels (ITLs) measured between January 2013 and December 2015 at two Canadian tertiary‐care centres were examined. The indications for TDM, clinical and laboratory disease activity indices and TDM‐driven treatment changes to infliximab therapy were documented. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…The published literature on the impact of TDM on decision making is limited. In a paediatric population,24 TDM resulted in change in management in 34% of cases. Another study of 71 patients reported a change in management for 37% of cases after TDM for SLR 9…”
Section: Discussionmentioning
confidence: 99%
“…The published literature on the impact of TDM on decision making is limited. In a paediatric population,24 TDM resulted in change in management in 34% of cases. Another study of 71 patients reported a change in management for 37% of cases after TDM for SLR 9…”
Section: Discussionmentioning
confidence: 99%
“…17 Consequently, the use of therapeutic drug monitoring in IBD patients on IFX has been gaining interest, with more utilization in clinical practice with emerging evidence suggesting better disease outcomes with a treat-to-target approach. 14,22,23 A systematic review that included 14 studies and examined the utility of TDM in children with IBD on anti-TNF agents concluded that TDM had a potential benefit and that incorporating measurements of infliximab trough levels at week 8 or week 14 predicted therapeutic responses and allowed for dose adjustments to reach therapeutic drug concentrations. However, a clinically relevant cutoff level of some anti-TNF agents has not been well defined yet, and the optimal intervention strategy still has to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, therapeutic drug monitoring (TDM) has been proposed as a means of optimizing biological therapies in both adults [70][71][72][73] and children [52,[74][75][76] with IBD. This approach appears to be more advantageous in pediatric patients, since fluctuations in pharmacokinetic variables tend to be more pronounced in children than in adults, possibly owing to physiological differences, such as volume of distribution, and immaturity of enzyme systems and of clearance mechanisms [52].…”
Section: Clinical and Biochemical Biomarkers Of Response To Anti-tnfs In Pibdmentioning
confidence: 99%